Beginning Java with Websphere - Janson, Robert W. (Expert's voice in Java., 2013)
Beginning Java with WebSphere provides a step-by-step guide for creating and installing both client- and server-based Java applications using Rapid Application Development v8, WebSphere Application Server 8.0, and Java.